Disparitäten der Lebensbedingungen - Persistenz oder raum-zeitlicher Wandel? Untersuchungen am Beispiel Süddeutschlands 1895 und 1980 - Thieme, Günter (ERDKUNDE, 1984)
Regional disparities of living conditions have been studied by social scientists as well as by Anglo-American geographers for some time, but little attention has been paid to this problem so far by German geographers. One of the main reasons for the growing interest in this field has been the increasing dissatisfaction with the gross national product as a measure of socioeconomic development. The terms social well-being, quality of life, and living conditions have frequently been used when attempts were made to replace the gross national product by more refined measures considering non-economic factors as well. This paper tries to demonstrate that the aspect of regional differentiation which is lacking in the majority of sociological contributions to this problem can be added by geographical research. Especially, the idea of Persistenz (roughly:continuity of traditional structures), a central concept of German social geography, may be successfully applied to the question of regional disparities. Using two social indicators, i.e. infant mortality and wages earned in manufacturing, differential living conditions and their temporal variations are discussed for the example of southern Germany in 1895 and 1980. At the close of the19th century there are considerable regional contrasts of infant mortality with a maximum of almost 43% of children dying in their first year. Among the factors used to explain the infant mortality differentials the crude birth rate and the type of feeding are most important, whereas medical care does not have a strong direct influence. On the whole, infant mortality may be interpreted as a syndrome of poverty and traditionalism. The wages of day-labourers serve as a second indicator of living conditions in 1895. The strong regional contrasts characterizing this variable, too, are analysed particularly in relation to the degree of industrialisation. Comparing today’s situation with that of 1895 the issue of the continuity of regional disparities over a long period is discussed in detail. By means of a multiple classification analysis it is possible to demonstrate that the historical variations of wages strongly affect the present wage and salary differentials, notwithstanding a substantial overall increase of wages in absolute numbers. In contrast to this, the present differences of the infant mortality rate, which in Germany has fallen to little more than 1% in 1982, have hardly any resemblance to the traditional regional pattern at the end of the19th century. There is no simple answer to the question whether there has been an increase or a levelling of regional disparities in living conditions. There is a certain trend towards a reduction of infant mortality differentials, but on the other hand, the spatial variation of wages and salaries today appears to be stronger than in 1895